2010
DOI: 10.1057/rlp.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence and conflicts between shopping malls and street markets in growing cities: Analysis of shoppers’ behaviour

Abstract: Street markets in developing countries constitute an integral part of the local economy as well as exhibiting the ethnic image of the habitat, which continues to function even in growing cities. The shopping malls have intercepted the traditional marketplace culture and are instrumental in shifting the consumer behaviour in urban areas. This article discusses how consumers ' decision-making styles shift towards shopping at malls as well as street markets in Mexico City. On the basis of exploratory data and usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 77 publications
4
29
1
5
Order By: Relevance
“…Findings are presented descriptively with some qualitative data in terms of percentages to support the analysis. Only five articles employ statistical techniques to investigate any causal relations (i.e., Agadjanian, ; Hiemstra, Van de Kooy, & Frese, ; Jaffe, Carciente, & Zanoni, ; Rajagopal, ; Reddy, ). Agadjanian () uses logistic regression analysis to test the effects of vendors’ individual characteristics on their relations with other vendors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings are presented descriptively with some qualitative data in terms of percentages to support the analysis. Only five articles employ statistical techniques to investigate any causal relations (i.e., Agadjanian, ; Hiemstra, Van de Kooy, & Frese, ; Jaffe, Carciente, & Zanoni, ; Rajagopal, ; Reddy, ). Agadjanian () uses logistic regression analysis to test the effects of vendors’ individual characteristics on their relations with other vendors.…”
Section: Resultsmentioning
confidence: 99%
“…Jaffe et al () test the correlation between credit demands and characteristics of vendors. Finally, Rajagopal () employs structural equation modeling to investigate consumer preferences toward shopping malls and street markets. Because of these limited quantitative results and diverse topics investigated, a meta‐analysis technique is not practical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that market choice and place are not necessarily based on product purchase but rather on social relationship and become more important when a social group consider losing its identify (Miller et al, 1998). Further, the consumer shopping behaviour and belief have an influence on the choice of a marketplace and affect the consumer decision towards shopping (Rajagopal, 2010). McColl-Kennedy and Kiel (2000) have found that in Australia's once influential strip malls became less dominant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interior structure and design of malls also had a potent impact on the wants of customers to stay more time in malls (Wakefield and Baker, 1998) and (Ooi and Sim, 2007) explain that a dreamy mall contains large amount of shops, beautiful and enjoyable environment to the customers. Street market are mostly give a cultural look than business network but the shopping malls is practically a business sector and provides a high standard life style to the urbans (Rajagopal, 2010). Malls can not only change the life style of consumer but also help the retailer to earn profit.…”
Section: Introductionmentioning
confidence: 99%